2015
DOI: 10.1111/papr.12402
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Female Smokers with Fibromyalgia on the Effects of Smoking on Fibromyalgia Symptoms

Abstract: Smokers with fibromyalgia reported smoking helped to cope with fibromyalgia pain but generally did not directly ameliorate fibromyalgia physical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Based on findings from our study, it is unclear whether smoking results in cognitive impairment or whether people with cognitive impairment use nicotine to cope with perceived cognitive dysfunction. For instance, a study by Weingarten et al revealed that most smokers who had FM used smoking to cope with pain symptoms via distraction and relaxation, to lessen emotional distress resulting from pain-induced frustration or sadness, and as justification for resting during smoking breaks 37 . Thus, it would be useful for future studies to explore the utility of medications that help patients quit smoking to assess whether cognitive deficits improve after cessation of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Based on findings from our study, it is unclear whether smoking results in cognitive impairment or whether people with cognitive impairment use nicotine to cope with perceived cognitive dysfunction. For instance, a study by Weingarten et al revealed that most smokers who had FM used smoking to cope with pain symptoms via distraction and relaxation, to lessen emotional distress resulting from pain-induced frustration or sadness, and as justification for resting during smoking breaks 37 . Thus, it would be useful for future studies to explore the utility of medications that help patients quit smoking to assess whether cognitive deficits improve after cessation of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies found that cigarette smoking is inversely associated with the risk of developing PD [25], and it has been postulated that the ease of smoking cessation is an early prodromal marker linked to a reduction in nicotine rewarding mechanisms [26]. Cigarette smoking is known to be more prevalent in FM patients, as it is in our cohort; it is possible that nicotine helps patients cope with the disease symptoms [27,28].…”
Section: Discussionmentioning
confidence: 84%
“…32 As with our study, this study of more than 400,000 veterans also found pain and symptom severity to be postively correlated to smoking status (current smoker, odds ratio [OR], 1.29) vs former smoker, OR, 1.02). 32 The association between chronic pain and smoking may reflect either the use of tobacco as a way to cope with pain, 12,33,34 continued smoking aggravating painful conditions, 33 or both. Smokers who are motivated to use tobacco to cope with or assuage pain may unwittingly aggravate their painful condition by increasing their cigarette consumption, thus entering into an endless cycle that could lead to greater nicotine dependence.…”
Section: Resultsmentioning
confidence: 99%
“…The association between chronic pain and smoking may reflect either the use of tobacco as a way to cope with pain, 12 , 33 , 34 continued smoking aggravating painful conditions, 33 or both. Smokers who are motivated to use tobacco to cope with or assuage pain may unwittingly aggravate their painful condition by increasing their cigarette consumption, thus entering into an endless cycle that could lead to greater nicotine dependence.…”
Section: Discussionmentioning
confidence: 99%